Exploratory factor analysis (efa) of social media attractiveness’ for MSMES - Vanessa Gaffar; Tika Annisa Koeswandi; Annisa Ciptagustia (Faculty of Economics and Business Mulawarman University, 2022)
This study aims to determine the factors that encourage MSMEs in using of social media that they can help them optimizing sustainable marketing activities in the era of digital transformation. This research is explanatory quantitative research where the aim is to reduce the number of variables, detect the structure of the relationship between variables, and classify them into a new group of variables. This research involves 9 variables/factors with 38 indicators. The data were taken through questionnaires and interviews with 317 food and beverage MSMEs in West Java. The data were analyzed through Explanatory Factor Analysis (EFA). The results of this study show the KMO Measure of Sampling (MSA) value is 0.939 and the Bartlett's Test value is 6850.368 with a significance number of 0.000. Then, the value of Anti Image Matrices on 38 indicators is above 0.5, so that all indicators are declared feasible. From Communalities in the attachment of factor analysis, it is known that the indicator X5.3 is the indicator that has the higest & strongest value (0.736) meanwhile the indicator X2.3 is the indicator that has the lowest & weakest value (0.377. According to the total initial eigenvalues, it is found that there are 6 factors that have values above 1. So that, in the rotated component matrix, each of 38 indicators put themselves into groups that have strong relationship. This study concludes that there are 6 main factors in encouraging SMEs in West Java to use social media, namely: earned benefit, communication, reliable, support tool, competition, price.